The Relationship Between Corpor Ate Governance And Corporate Social Responsib Ility In Governm Ent Linked Companies In Malaysia - J Nulawadin, Nor Shafinaz (2008)

(untitled)
The purpose of this study is to examine whether Corporate Governance and Board of Directors will have influence on the level of Corporate Social Responsibility in Government-Linked Companies in Malaysia.